2002
DOI: 10.1080/080352502320777397
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant improves oxygenation in infants and children with pneumonia and acute respiratory distress syndrome

Abstract: Surfactant dysfunction probably plays a role in the pathophysiology of severe paediatric ARDS triggered by pneumonia, as it was found that surfactant instillation rapidly improved gas exchange in the majority of the affected infants in our study. Larger randomized controlled studies are necessary to evaluate the effects of surfactant treatment on morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…The improvement in oxygenation in the surfactant treatment group in our study is consistent with trials conducted in the past in both animal (22-28) and human (15,29-31) models. The mechanism of induced injury and surfactant used were different in the various studies; however, most studies reported an improvement in oxygenation (32).…”
Section: Discussionsupporting
confidence: 91%
“…The improvement in oxygenation in the surfactant treatment group in our study is consistent with trials conducted in the past in both animal (22-28) and human (15,29-31) models. The mechanism of induced injury and surfactant used were different in the various studies; however, most studies reported an improvement in oxygenation (32).…”
Section: Discussionsupporting
confidence: 91%
“…The mechanism of action is believed to involve leakage of surfactant inhibitors and/or plasma proteins into the bronchoalveolar space, causing a secondary surfactant deficiency or inactivation. 4,28,29 It has thus been postulated that surfactant replacement could improve clinical respiratory status by improving deranged pulmonary mechanics.…”
Section: Bacterialmentioning
confidence: 99%
“…Surfactant administration via an endotracheal tube has been investigated as a treatment option in (small, non-randomized) clinical trials on mechanically ventilated pediatric patients suffering from ARDS [23, 24] showing improved oxygenation as an acute effect. The only controlled trial on surfactant treatment in pediatric ARDS did not show a beneficial effect on the duration of mechanical ventilation [25].…”
Section: Discussionmentioning
confidence: 99%